The influence of 17β-estradiol plus norethisterone acetate treatment on markers of glucose and insulin metabolism in women: a systematic review and meta-analysis of randomized controlled trials - Cui, Weijuan; Zhao, Ling (Frontiers in Endocrinology, 2023)
Objective: Despite the fact that some evidence suggests that the administration of 17β-estradiol plus norethisterone acetate influences glucose and insulin metabolism in women, these findings are still contradictory. Thus, we aimed to examine the impact of the co-administration of 17β-estradiol and norethisterone acetate on glycated haemoglobin (HbA1c), fasting glucose, insulin and C-peptide concentrations in females by means of a systematic review and meta-analysis of randomized controlled trials (RCTs). Methods: We searched four databases (PubMed/MEDLINE, Scopus, Embase, and Web of Science) using specific keywords and word combinations. The random-effects model (DerSimonian and Laird model) was employed to compute the weighted mean difference (WMD) and 95% confidence intervals (CIs) for the variations from baseline of HbA1c, fasting glucose, insulin, and C-peptide concentrations. Results: In total, 14 RCTs were entered into the quantitative synthesis. The combined administration of 17β-estradiol and norethisterone acetate decreased HbA1c (WMD: -0.65%, 95% CI: -1.15 to -0.15; P=0.011), fasting glucose (WMD: -11.05 mg/dL, 95% CI: -16.6 to -5.5; P<0.001) and insulin (WMD: -1.35 mIU/L, 95% CI: -2.20 to -0.50; P=0.001) levels. C-peptide concentrations’ declined only in females diagnosed with overweight/obesity or diabetes. Conclusion: Evidence to date points out that the administration of 17β-estradiol and norethisterone acetate has a positive impact on glucose metabolism in women by reducing fasting glucose, HbA1c, and insulin values. Future studies need to confirm the potential benefits of this drug combination in the prevention and/or management of cardiometabolic disorders.